The Correlation between Sleep Hygiene and Sleep Disorders among Adolescents - Arizsyah, Dliyaul Awlia; Awalin, Fischa; Hakim, Nuraini; Setyawati, Anita (Journal of Nursing Care, 2026)
Sleep difficulties are prevalent among adolescents and can impact physical and mental health, along with academic performance. Prior research has demonstrated a correlation between sleep hygiene, a set of measures designed to create a regular sleep regimen, and sleep problems. This study seeks to ascertain the correlation between sleep hygiene and sleep problems in teenagers. This study employed a quantitative research design utilizing a cross-sectional technique and was done with 50 adolescents at a school in Tangerang. The sampling was conducted with a simple random sampling method facilitated by a spinner program. Data were collected by the administration of the Sleep Hygiene Index (SHI) and the Children's Sleep Habits Questionnaire (CSHQ), and subsequently analyzed utilizing a chi-square test. The findings indicated a correlation between sleep hygiene and sleep problems in teenagers (α = 0.008). A significant proportion of respondents exhibited inadequate sleep hygiene and sleep disorders, with rates of 86% and 80%, respectively. The psychological state of teenagers transitioning to adulthood also influences sleep hygiene and sleep disorders. Parents, educators, and school health professionals must educate teenagers about managing sleep disorders through the enhancement of sleep hygiene practices.